Secondary School Students’ Acceptance Towards Ppda And Its Relation With Their Attitude Towards Illicit Drug - Nur Hidayah Binti Salleh
The student is the next generation who will lead the country in the future. Therefore, the country needs to produce a free generation from drug abuse. Therefore, this research aims to identify the level of acceptance of secondary school students towards the PPDa program with attitudes toward illicit drugs. A total of 380 Form 4 and 5 students were selected as respondents. A pilot study was conducted to see the reliability and appropriateness of the questionnaire. Cronbach's Alpha reliability values for the entire questionnaire are 0.954 and 0.916. The questionnaire used in this study contains 35 items consisting of 20 items to measure the level of acceptance of high school students towards the PPDa program and 15 items to measure students' attitudes towards illegal drugs. Descriptive statistics measured high school students' acceptance of the PPDa program and attitudes toward illegal drugs. The researcher examined the differences between the sexes using independent t-test analysis and the differences in socioeconomic status using one-way ANOVA analysis. While inferential statistics, namely Pearson's correlation, is used to measure the relationship between the level of acceptance of high school students towards the PPDa program and attitudes toward illegal drugs. The study's findings show no significant difference in the level of high school students' acceptance of the PPDa program and attitudes towards illicit drugs based on gender. However, the findings show a significant difference in the level of acceptance of secondary school students towards the PPDa program and attitudes towards illicit drugs based on socioeconomic status. Pearson's correlation analysis shows no significant relationship between high school students' acceptance of the PPDa program and attitudes towards illegal drugs. Several suggestions have been presented, and all the information obtained in this study can be used by the parties concerned for a more in-depth follow-up study.